Potential Use of Jackfruit (Artocarpus Heterophyllus) and Breadfruit (Artocarpus Altilis) as Fat Replacer to Produce Low-Fat Chicken Patties - Rashedi Ismail-Fitry, Mohammad; Farihah Azwa Abas, Nur (International Journal of Engineering and Technology, 2019)
Commercial chicken patties contain high fat, which could affect consumers’ health. Jackfruit (Artocarpus heterophyllus) and breadfruit (Artocarpus altilis) may have the potential to be used as the fat replacer in the chicken patties. This study aimed to evaluate the low-fat chicken patties produced by replacing the fat with jackfruit (JF) or breadfruit (BF) at 0% (control), 50% and 100%. The samples were analysed in terms of water holding capacity (WHC), cooking yield (CY), proximate analysis, colour, texture properties, and sensory parameters. Both BF and JF showed higher value (p<0.05) for WHC, moisture content and protein compared to the control. BF (100%) and JF (100%) were recorded of having significantly reduced fat (p<0.05) at 1.80% and 2.23%, respectively. BF showed higher L*(lightness) and b*(yellowness) values significantly (p<0.05) compared to the control. Not many significant differences (p>0.05) between the control and newly formulated chicken patties texture based on the hardness, cohesiveness, and chewiness recorded, proving that BF and JF did not affect the patties texture. Overall, the sensory evaluation of BF (100%) was preferred by the consumer in terms of appearance, texture, flavour, juiciness, and aroma. Thus, BF (100%) can be considered as the best fat replacer in this study.